2019
DOI: 10.1111/crj.13019
|View full text |Cite
|
Sign up to set email alerts
|

Impaired glucose tolerance, body mass index and respiratory function in patients with cystic fibrosis: A systematic review

Abstract: Objectives This systematic review aims to evaluate body mass index (BMI) and forced expiratory volume in one second (FEV1) in patients with cystic fibrosis (CF) diagnosed with impaired glucose tolerance (IGT) compared to those with normal glucose tolerance (NGT). The significance of this topic stems from concern that individuals with CF and IGT may have an overall worse clinical status as indicated by BMI and FEV1. Data Source An exhaustive literature search was completed between July 2017 and September 2017 u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
0
2
0
3
Order By: Relevance
“…CFRD can cause poor growth and increase the risk of pulmonary exacerbations due to hyperglycaemia promoting bacterial growth and increased thickness of secretions 4 . Of note, a systematic review in 2019 6 showed no difference in Body Mass Index (BMI), Forced Expiratory Volume in 1 second (FEV 1 ) in patients with CF and impaired glucose tolerance when compared to those with normal glucose tolerance. Investigations to diagnosed diabetes include HbA1c and OGTT.…”
Section: Improving Screening In a Paediatric Cohort For Cystic Fibros...mentioning
confidence: 99%
“…CFRD can cause poor growth and increase the risk of pulmonary exacerbations due to hyperglycaemia promoting bacterial growth and increased thickness of secretions 4 . Of note, a systematic review in 2019 6 showed no difference in Body Mass Index (BMI), Forced Expiratory Volume in 1 second (FEV 1 ) in patients with CF and impaired glucose tolerance when compared to those with normal glucose tolerance. Investigations to diagnosed diabetes include HbA1c and OGTT.…”
Section: Improving Screening In a Paediatric Cohort For Cystic Fibros...mentioning
confidence: 99%
“…Отмечено, что показатель ОФВ 1 начинает снижаться за 2-4 года до постановки МЗСД [2,3,15]. Доказано, что снижение функции легких является ведущей причиной заболеваемости и смертности пациентов с МЗСД [5,19,20]. Следует отметить, что макро-и микрососудистые осложнения, в отличие от других типов СД, при МЗСД встречаются редко и не являются основной причиной смерти [5,20].…”
Section: Introductionunclassified
“…Получены неоднозначные данные, свидетельствующие об изменении ОФВ 1 и ИМТ. В одних исследованиях показано, что в предиабетический период уже отмечается снижение ОФВ 1 и ИМТ [19,27], в других исследованиях данных за изменения ОФВ 1 и ИМТ не получено [19]. Очевидно, что своевременное выявление НУО в период предиабета у детей с МВ является трудной и малоизученной задачей.…”
Section: Introductionunclassified
“…МЗСД обычно предшествуют преддиабетические состояния, в т. ч. нарушение гликемии натощак (НГН), неопределенная гликемия (indeterminate glycemia (INDET) и нарушение толерантности к глюкозе (НТГ) [4,5,10]. Согласно российским Клиническим рекомендациям по ведению взрослых и детей с кистозным фиброзом, опубликованным в 2021 г., и данным Американской диабетической ассоциации, диагностическим скринингом углеводного обмена является 2-часовой оральный глюкозотолерантный тест, который рекомендуется ежегодно проводить детям, начиная с 10-летнего возраста, а в некоторых случаях по показаниям тест может проводится и в более раннем возрасте [11,12] (табл.…”
Section: Introductionunclassified